Embryonic T-box transcription factor Brachyury as a predictive biomarker and therapeutic target in prostate and lung cancers - Fontão, Patrícia Fernandes (2021)
Dissertação de mestrado em Applied Biochemistry (área de especialização em Specialization in Biomedicine)